Effect of hydroponic cultivation using MPM-processed methane fermentation digestate on tomato growth and yield - Rachma, Dannisa Fathiya; Maeda, Kazuya; Yamanouchi, Yuta; Ueda, Hiroshi; Yamamoto, Kimiko; Shinohara, Makoto; Isozaki, Masahide; Ahn, Dong-Hyuk (Frontiers in Horticulture, 2026)
IntroductionLiquid digestate produced from manure-based methane fermentation contains organic and inorganic forms of nitrogen, phosphorus, potassium, and other micronutrients that have potential as plant nutrients, but its use in soilless horticulture requires appropriate microbial processing due to high ammonium concentrations and possible salinity-related constraints. Ammonium (NH4+), the predominant nitrogen form in methane fermentation digestate, must be converted to nitrate (NO3-) by nitrifying microorganisms before application in hydroponic systems. The multiple parallel mineralization (MPM) method enables controlled microbial nitrification of digestate nitrogen.MethodsIn this study, MPM-processed methane fermentation digestate (MPM digestate) generated nitrate through microbial nitrification, maintaining an average nitrate–nitrogen concentration of approximately 226 mg L-¹ in the hydroponic nutrient solution throughout the cultivation period. Yield components of the tomato cultivar ‘Momotaro Hope’ grown in an open hydroponic system were compared between MPM-digestate and chemical fertilizer (CF) treatments for up to 124 days after transplanting (DAT), corresponding to the harvest of the seventh fruit truss.ResultsWhile total season yield and fruit quality parameters, including total soluble solids (TSS), lycopene, and γ-aminobutyric acid (GABA), did not differ significantly between treatments, plant growth responses varied temporally. The cultivation period was divided into three growth stages (Stages I–III) based on key growth indicators. During Stage III (88–124 DAT), the MPM-digestate treatment exhibited significantly lower total dry matter (TDM), light use efficiency (LUE), and stage-specific cumulative yield than the CF treatment, although the proportion of dry matter allocated to fruit was 18% higher under MPM digestate during this stage.DiscussionThese late-stage reductions may be associated with elevated electrical conductivity (EC) in the drainage solution observed during Stage II (34–87 DAT) under the MPM-digestate treatment. Increased EC values approaching 5 mS cm-¹, likely influenced by elevated Na+ and Cl- concentrations, may have induced osmotic stress or ion-specific nutrient imbalances that affected subsequent plant performance.ConclusionMPM-processed methane fermentation digestate can be utilized in hydroponic tomato cultivation when drainage EC is carefully managed, achieving fruit quality comparable to conventional fertilization, although late-stage biomass accumulation and yield may be reduced under elevated salinity conditions.